Variability of clinical syndromes and cerebral glucose metabolism in symptomatic frontotemporal lobar degeneration associated with progranulin mutations. Issue 5 (2nd July 2020) - Licata, Abigail; Grimmer, Timo; Winkelmann, Juliane; Wagner, Matias; Goldhardt, Oliver; Riedl, Lina; Roßmeier, Carola; Yakushev, Igor; Diehl-Schmid, Janine
Abstract: Objective : The aims of our study were to describe the clinical phenotype and to characterize the cerebral glucose metabolism patterns as measured with fluordesoxyglucose-positron emission tomography (FDG-PET) in symptomatic FTLD-patients with different GRN variants. Methods : For this study, data were included from all patients ( n = 10) of a single-center FTLD registry study who had a pathogenic GRN variant and who had undergone a cerebral FDG-PET scan. Results : An overt variability of clinical phenotypes was identified with half of the cases being not unambiguously classifiable into one of the clinical FTLD subtypes. Furthermore, GRN + patients showed a considerable inter-individual variability of FDG uptake pattern. In half of the GRN + patients, metabolic changes expanded from frontal and temporal brain regions to parietal brain regions including the posterior cingulate cortex. Striking asymmetry without a preference for either hemisphere was overt in half of GRN + cases. Conclusion : We conclude that GRN mutations cause variable patterns of neurodegeneration that often exceed the anatomical boundaries of the frontotemporal brain regions and produce clinical syndromes that cannot clearly be classified into one of the subtypes as defined by the diagnostic criteria.